The association between major depressive disorder and generalized anxiety disorder with hematological indices in the Rafsanjan youth cohort study - Zahra Jamali; Reza Hosseiniara; Parvin Khalili; Mohammadreza Mirazaei; Sadegh Zarei; Mostafa Habibi; Mojgan Noroozi Karimabad (Scientific Reports)
Abstract Depression and anxiety disorders appear to be associated with alterations in hematological indices, as well as increased systemic inflammation. This study aimed to investigate the association between major depressive disorder (MDD) and generalized anxiety disorder (GAD) with hematological indices in the youth population of Rafsanjan, Iran. This cross-sectional study involved a sample of 3006 urban and rural youth aged 15 to 35 who participated in the initial phase of the Rafsanjan youth cohort study ((RYCS), with relevant data available in the cohort database. The presence of MDD and GAD was confirmed and recorded using the composite international diagnostic interview version 2.1 tool. Data were collected on age, sex, education level, body mass index, history of smoking, opium or alcohol use, intensity of physical activity, and history of diabetes or hypertension. Hematological indices result, including RBC, WBC, HGB, HCT, MCV, MCH, MCHC, PLT, RDW, MO, GR, LY, PDW, and MPV, were extracted from the cohort system. The associations between hematological indices and MDD and GAD were evaluated using crude and adjusted models in linear regression analysis. A total of 2,939 young adults with a mean age of 25.77 ± 6.04 (55.97% females) were evaluated. The prevalence of MDD was found to be 14.9%, while the prevalence of GAD was 7.49%. In linear regression analysis, a negative association was observed between RDW (β=−0.1, [−0.18, −0.01], p = 0.022) and a positive association between NLR (β = 0.097, [0.01, 0.18], p = 0.031) with MDD in males; however, no significant associations were found between hematological indices and MDD in females. Conversely, RDW (β = −0.15, [−0.28, −0.02], p = 0.029) exhibited a negative association and MPV (β = 0.1, [0.003, 0.201], p = 0.046) and HCT (β = 0.494, [0.114, 0.974], P = 0.044) positive associations with GAD in females. In males, NLR (β = 0.22, [−0.09,–0.034], p = 0.001) showed a positive association and the percentage of lymphocytes (β=−2.71, [−5.39, −0.136], p = 0.029) a negative association with GAD. The findings indicate that RDW and NLR values are significantly related to MDD in males, while HCT, RDW and MPV values are significantly related to GAD in females. Additionally, NLR values and the percentage of lymphocytes are significantly related to GAD in males. To verify these associations, further studies with longitudinal design are needed.